Early Pregnancy Examination Education as an Effort for Delivery Complications - Imelda Iskandar; Dewiyanti; Suradi Efendi; Nour Sriyanah (PT Inovasi Pratama Internasional, 2022)
Antenatal care is defined as health services provided to pregnant women by family members or midwives during the entire pregnancy. Care during pregnancy is important for the proper growth and development of the baby. Prenatal care helps reduce or prevent adverse outcomes during pregnancy. Poor antenatal care causes low birth weight babies, premature babies, neonatal deaths, birth complications etc. It is also effective in reducing maternal morbidity that occurs due to poor health, an unhygienic environment, poor nutrition and lack of medical facilities. Maternal Mortality Rate (MMR) is the number of maternal deaths that occur during pregnancy, childbirth, postpartum caused by emergency complications, either directly or indirectly . Factors that cause maternal death can be broadly grouped into direct and indirect causes. One of the efforts to accelerate the reduction of maternal and newborn mortality is through increasing access and quality of antenatal care, delivery assistance, prevention of complications and family planning by midwives, better known as the Childbirth Planning and Complications Prevention Program (P4K) programmed by the Indonesian Ministry of Health. The method of this community service is the counseling method in the form of direct presentation of lecture material to pregnant women and distributing questionnaires to assess the level of knowledge of mothers related to early pregnancy checks in an effort to prevent childbirth complications that occur in pregnant women. The importance of disseminating information related to antenatal care for the prevention of complications during delivery is very important for pregnant women to reduce maternal and infant mortality.